Validity and Practicality of Flipped Classroom Based on Guided Inquiry on Reaction Rate Material - Aprilia Ninda; Mawardi Mawardi (Universitas Negeri Padang, 2022)
Indonesia is entering the era of the industrial revolution 4.0 which is marked by advances in the field of technology. Teachers are required to have the ability to integrate technology into the learning process. In addition, the reaction rate material is classified as a material that is difficult to understand because the material is abstract. For that we need an appropriate learning system. Then a guided inquiry-based flipped classroom learning system was developed using Moodle on the reaction rate material. The type of research conducted is educational design research (EDR) with a plomp development model. Based on the research conducted, it was found that the level of content and media validity of the flipped classroom learning system based on guided inquiry was 0.89 and 0.93 with valid categories. While the level of practicality of teachers and students is 0.90% and 0.91% with a very practical category.